PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN KIMIA SCIENCE BERBASIS WEBSITE PADA MATERI STOIKIOMETRI TERHADAP HASIL BELAJAR SISWA KELAS X DI SMA SANTO PAULUS PONTIANAK - Harjulianto, Feri; Hairida, Hairida; Sartika, Rody Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to determine the influence of site-based chemistry learning on the study results of chemistry class of 10 grade students. Based on the field observations, there are lack of utilization of information technology to help the learning process, thus, if supported by adequate facilities and infrastructure, it is appropriate to use the use of information technology in this case Chemistry sites-based learning to help the process of study for the high school students of grade 10th on chemistry Stoichiometry material. This research was conducted in SMA Santo Paul Pontianak in the first semester of 2017/2018. TheÂ  esearchmethod used is quasi experiment with Nonequivalent Kontrol Group Design research design. Instrument used to measure the learning outcomes is a multiple choice test conducted before (pre-test) and after giving treatment (post-test). The analysis of post test data from both groups using t-test and obtained value of .sig 0.005 <0.05. It can be concluded that Ha is accepted and Ho is rejected which means there are significant differences to the learning outcomes in the experimental class and control class.Keywords : site-based chemistry, website, the study results, Stoichiometry